OSRA Grant Cycle 1 Public Reports : Project Title: Mothers in Lebanon: Unraveling their Family’s Structure, Characteristics, Demands and Resources of Support - Khalid Yunis (2838812) (2019)
This study investigates the intricate relationship between family structures and demographic changes in the Arab world, with a particular focus on Lebanon. Recent empirical evidence highlights the significant role of family dynamics in shaping children's cognitive, socio-emotional, and physical well-being. The Arab family, while adapting to modernization, maintains its unique characteristics and fosters a strong interdependence between individuals and the family unit. The research examines family configurations, maternal support sources, and well-being priorities among Lebanese and displaced Syrian mothers in diverse Lebanese regions, reflecting the cultural diversity of the Arab world. Additionally, the study acknowledges the influence of demographic shifts, such as aging populations, youth unemployment, and changing mortality and fertility rates, on the emergence of new family structures. This comprehensive exploration aims to provide valuable insights into family characteristics and support systems, leveraging Lebanon's unique socio-political context, shaped by the Syrian Crisis. Ultimately, the research findings have the potential to inform policy decisions at various levels throughout the Arab world.